Evaluation of the periodical collections of selected Protestant theological seminary libraries in the Philippines - Calig, Elvira Virginia L. (1994)
This study evaluated the periodical collections of selected Protestant theological seminary libraries in the Philippines. The primary purpose is to evaluate the sufficiency of the periodical collections in supporting the instructional needs of the theological seminaries. The impressionistic method was used, utilizing faculty and students' perceptions about the periodical collections in relation to their personal needs, information needs, and in relation to the curricular requirements of the graduate program of the theological schools.